The impact of climate change on pastoral production systems: A study of climate variability and household adaptation strategies in southern Ethiopian rangelands - Wassie Berhanu; Fekadu Beyene (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper examines the determinants and implied economic impacts of climate change adaptation strategies in the context of traditional pastoralism. It is based on a household level survey in southern Ethiopian rangelands. Pastoralists' perception of climate change in the region is found to be very consistent with the actually recorded trends of increased temperature and the evident secular declines in precipitation. Not only long-term declines, trends in the region's rainfall also appear to have taken a direction of more shifts towards unpredictability. Pastoralist adaptation response strategies broadly involve adjustments in pastoral practices and shifts to non-pastoral livelihoods. Results of the estimated models confirm that pastoral mobility is still quite essential in the present context of climate-induced household vulnerabilities. Increased mobility and diversification of pastoral herd portfolios in favor of a drought-tolerant species (camel) are found to have highly significant positive impact on pastoral productivity. A policy stance that ignores the detrimental impacts of the currently pervasive private rangeland enclosures or intends to hasten pastoralist sedentarization in the area is simply untenable in the present context of climate-induced risks and pastoral livelihood vulnerability.
Keywords: O13; Q54; Z13; 330; climate change; pastoralism; adaptation strategies; Borana; Ethiopia